Coherent precipitation and stability of cuboidal nanoparticles in body-centered-cubic Al0.4Nb0.5Ta0.5TiZr0.8 refractory high entropy alloy. (1st January 2021) - Wang, Qing; Han, Jincan; Liu, Yufeng; Zhang, Zhongwei; Dong, Chuang; Liaw, Peter K.
Abstract: The present work developed a new body-centered-cubic (BCC)-based Al0.4 Nb0.5 Ta0.5 TiZr0.8 refractory high entropy alloy with coherent precipitation. The formation of cuboidal nanoprecipitates with a size of 25~50 nm in an 873 K-aged alloy is ascribed to a moderate lattice misfit. A Zr5 Al3 phase also coexists with B2 in a same particle shape due to similar chemical compositions, in which Ti is enriched in B2 but not in Zr5 Al3 . The BCC/B2 coherency would be deteriorated with increasing the aging temperature, leaving coarse Zr5 Al3 alone. Besides, there exist two kinds of BCC phases due to the segregations of Nb/Ta and Ti/Zr. Graphical abstract: Image, graphical abstract